2021
DOI: 10.3390/v13061173
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Human Papillomaviruses in Head and Neck Cancer—What Remains in 2021 from a Clinician’s Point of View?

Abstract: Human papillomaviruses (HPV) cause a subset of head and neck cancers (HNSCC). HPV16 predominantly signs responsible for approximately 10% of all HNSCC and over 50% of tonsillar [T]SCCs. Prevalence rates depend on several factors, such as the geographical region where patients live, possibly due to different social and sexual habits. Smoking plays an important role, with non-smoking patients being mostly HPV-positive and smokers being mostly HPV-negative. This is of unparalleled clinical relevance, as the outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 95 publications
0
8
0
1
Order By: Relevance
“…HPVs have less than 90% resemblance to other nucleotide levels. 9 , 10 More than 150 genotypes of HPV have been identified by DNA sequencing and were stratified according to oncogenic risk. Seventeen genotypes are clearly linked to the development of adenocarcinoma and squamous cell carcinoma of the cervix and therefore were ranked as high-risk HPV: −16, −18, −31, −33, −35, −39, −45, −51, −52, −53,56, −58, −59, −66,-68, −73, and −82.…”
Section: Introductionmentioning
confidence: 99%
“…HPVs have less than 90% resemblance to other nucleotide levels. 9 , 10 More than 150 genotypes of HPV have been identified by DNA sequencing and were stratified according to oncogenic risk. Seventeen genotypes are clearly linked to the development of adenocarcinoma and squamous cell carcinoma of the cervix and therefore were ranked as high-risk HPV: −16, −18, −31, −33, −35, −39, −45, −51, −52, −53,56, −58, −59, −66,-68, −73, and −82.…”
Section: Introductionmentioning
confidence: 99%
“…The International Agency for Research on Cancer (IARC) under the World Health Organization (WHO) has classified the mucosotropic alpha‐genus HPV genotypes into high‐risk (HPV16, 18, 31, 33, 35, 39, 45, 51, 52, 56, 58, and 59) and low‐risk (HPV6 and 11, among others) genotypes based on their carcinogenic potential in the uterine cervix (International Agency for Research on Cancer, 2012a ). Of the high‐risk genotypes, HPV16 and 18 harbor the highest malignant potential, which together are responsible for more than 70% of all cervical carcinomas and 95% of all oropharyngeal SCC (Bonde et al, 2020 ; Hoffmann & Quabius, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of HPV has been studied in different countries (3). Some studies have indicated an association between HPV and other cancers, such as lung, breast, esophageal, colon and rectum, and prostate cancers; however, a recurrent causal relationship between these cancers and the virus has not been shown (4,5).…”
Section: Introductionmentioning
confidence: 99%